Visualization of properties of phase-shifting algorithms - Edward Christopher (Nanyang Technological University, 2020)
The advancement of computer science, especially in conjunction with optical sciences, has led to a high demand for high precision optical testing. High precision optical testing is normally performed through a method known as interferometry, where surfaces of optical devices are mapped through the interference of 2 or more light waves. Phase Shifting Interferometry (PSI) is a one of the most widely used interferometry techniques for optical testing. PSI uses multiple interferograms introduced by means of a phase shift as opposed to a static interferogram in determining the phase value related to the surface of the tested optical devices. In order to find phase value, PSI uses PSI algorithms which utilizes the intensity values of from the interferograms, in order to reconstruct the tangent of the tested phase, which can be used to obtain phase value. Various PSI algorithms have been developed throughout the years as means to develop an algorithm resistant to various error sources. This project aims to develop a visualization application to illustrate PSI algorithm properties when exposed to different types of error. A web-based application consisting of a Backend REST API in conjunction with a Frontend Web Application is developed to support this aim. This web application is specially designed in order to be able to demonstrate an interactive and intuitive PSI 3D model for PSI phase errors. In the near future, this web application can be improved through incorporating better design ideas as well as providing integration with other platforms.